Characterization of serum biomarkers and antibody responses against Prevotella spp. in preclinical and new-onset phase of rheumatic diseases - Amend, Lena; Gilbert, Benoît Thomas P.; Pelczar, Penelope; Böttcher, Marius; Huber, Samuel; Witte, Torsten; Finckh, Axel; Strowig, Till (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The characterization of the influence of the microbiota on the development and drug responses during rheumatic diseases has intensified in recent years. The role of specific bacteria during disease development has become a central research question. Notably, several lines of evidence point to distinct microbes, e.g., Prevotella copri (P. copri) being targeted by antibodies in clinical phases of rheumatic diseases. Methods In the present study, we compiled a broad collection of human serum samples from individuals at risk of developing RA, chronic RA patients as well as patients with new-onset of rheumatic diseases. We evaluated the presence of inflammatory biomarkers in our serum collection as well as serum antibody responses against novel, genetically distinct isolates of P. copri and several oral pathobionts. Results Our analysis revealed the presence of increased levels of inflammatory markers already in pre-clinical and new onset rheumatoid arthritis. However, antibody reactivity against the microbes did not differ between patient groups. Yet, we observed high variability between the different P. copri strains. We found total serum IgG levels to slightly correlate with IgG antibody responses against P. copri, but no relation between the latter and presence or prevalence of P. copri in the intestine. Discussion In conclusion, our work underlined the importance of strain-level characterization and its consideration during further investigations of host-microbiota interactions and the development of microbiome-based therapeutic approaches for treating rheumatic diseases.